Topological Studies of the Amino Terminal Modules of Vitamin K-dependent Protein S Using Monoclonal Antibody Epitope Mapping and Molecular Modeling - Giri, Tusar K.; Villoutreix, Bruno O.; Wallqvist, Anders; Dahlbäck, Björn; Frutos, Pablo García de (Thrombosis and Haemostasis, 1998)
Protein S is an important anticoagulant protein acting as cofactor to activated protein C (APC) in the degradation of membrane-bound factors Va and VIIIa. Binding of protein S to the membrane depends on the Gla-domain, whereas sites for APC-interaction are located in the thrombin-sensitive region (TSR) and the first EGF domain. The aims of the present investigation were to localize the sites on protein S which are involved in APC-cofactor function and to elucidate possible orientations of the TSR in relation to the membrane. For these purposes, we determined the epitope for a calcium-dependent monoclonal antibody (HPS67) against the TSR, which inhibits APC cofactor activity even though it does not impede protein S binding to the membrane. HPS67 did not recognize wild-type mouse protein S but gained reactivity against a recombinant mouse protein in which G49 and R52 were mutated to R and Q (found in human protein S), respectively, suggesting these two residues to be part of a surface exposed epitope for HPS67. This information helped in the validation and refinement of the structural model for the Gla-TSR-EGF1-modules of protein S. The X-ray structure of a Fab-fragment mimicking HPS67 was docked onto the protein S model. The observation that HPS67 did not inhibit phospholipid binding of protein S has implications for the possible orientation of protein S on the membrane surface. In the proposed model for membrane-bound protein S, there is no contact between the TSR and the membrane. Rather, the TSR is free to interact with membrane-bound APC.